Islamic Religious Education Teachers' Strategies in Implementing Process Differentiation in Islamic Cultural History Learning - Maspuroh Maspuroh; Sofiatul Aminah (Pasundan Social Science Development, 2026)
This research is motivated by the learning conditions of Islamic Cultural History (ISCR) at SMA Negeri 1 Ciranjang, which still tends to be monotonous and has not adapted to the diverse learning styles of students, resulting in low understanding and motivation to learn. The purpose of this study is to determine the strategies of Islamic Education teachers in implementing process differentiation, its implementation in grade XI, and the form of student understanding of ISCR material. This study uses a qualitative approach with a field study method, through observation, interviews, and documentation techniques. The results show that teachers apply process differentiation strategies through methods such as group discussions and mind mapping that are adapted to student characteristics. The implementation of this strategy has been proven to increase student engagement and understanding. Thus, process differentiation can be an effective approach in creating more adaptive and meaningful ISCR learning.